Al-'Ilm Al-udhri: Philosophical Epistemology and Sufism Common Ground - Walid, Kholid Al; Darmawan, Darmawan; Barra, Ni'mah Umm Hani D.; Norman, Nurul Ain (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2023)
This article investigates the possibility of finding common ground between philosophy and Sufism. It aims to answer whether these two can converge on an epistemological level. The discourse of al-'ilm al-áº–udhÅ«riÂ  was used to answer this question. The main source for this article's study is the works of Mulla Sadra and Suhrawardi, which are analyzed descriptively with a philosophical approach. This article concludes that al-'ilm al-áº–udhÅ«ri is a form of real knowledge obtained by individuals directly from God without needing mental representation or linguistic symbolism. This knowledge is spiritual, not sensory-rational. Mulla Sadra and Suhrawardi believe that the only way to obtain this knowledge is through spiritual observation by practicing Sufism, which involves the rites of mujahadah and riyadhah.